Development and validation of simple spectrophotometric and chemometric methods for simultaneous determination of empagliflozin and metformin: Applied to recently approved pharmaceutical formulation - Ayoub, Bassam M. (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2016)
New univariate spectrophotometric method and multivariate chemometric approach were developed and compared for simultaneous determination of empagliflozin and metformin manipulating their zero order absorption spectra with application on their pharmaceutical preparation. Sample enrichment technique was used to increase concentration of empagliflozin after extraction from tablets to allow its simultaneous determination with metformin without prior separation. Validation parameters according to ICH guidelines were satisfactory over the concentration range of 2–12μgmL−1 for both drugs using simultaneous equation with LOD values equal to 0.20μgmL−1 and 0.19μgmL−1, LOQ values equal to 0.59μgmL−1 and 0.58μgmL−1 for empagliflozin and metformin, respectively. While the optimum results for the chemometric approach using partial least squares method (PLS-2) were obtained using concentration range of 2–10μgmL−1. The optimized validated methods are suitable for quality control laboratories enable fast and economic determination of the recently approved pharmaceutical combination Synjardy® tablets. [Display omitted] •Simultaneous determination of empagliflozin and metformin•First spectrophotometric method for determination of empagliflozin and metformin•First chemometric method for determination of empagliflozin•Applicable on recently approved pharmaceutical dosage form•The proposed method is suitable for QC laboratories